Revisiting poverty trends and the role of social protection systems in Africa during the COVID-19 pandemic - Abay, Kibrom A.; Yonzan, Nishant; Kurdi, Sikandra; Tafere, Kibrom (Oxford University Press, 2023)
Quantifying the impact of the COVID-19 pandemic on poverty in Africa has been as difficult as predicting the path of the pandemic, mainly due to data limitations. The advent of new data sources, including national accounts and phone survey data, provides an opportunity for a thorough reassessment of the impact of the pandemic and the subsequent expansion of social protection systems on the evolution of poverty in Africa. In this paper, we combine per capita GDP growth from national accounts with data from High-Frequency Phone Surveys for several countries to estimate the net impact of the pandemic on poverty. We find that the pandemic has increased poverty in Africa by 1.5 to 1.7 percentage points in 2020, relatively smaller than early estimates and projections. We also find that countries affected by Fragility, Conflict and Violence experienced the greatest increases in poverty, about 2.1 percentage points in 2020. Furthermore, we assess and synthesize empirical evidence on the role that social protection systems played in mitigating the adverse impact of the COVID-19 crisis in Africa. We review social protection responses in various African countries, mainly focusing on the impact of these programs and effectiveness of targeting systems. Although the evidence base on the protective role of social protection programs during the pandemic remains scarce, we highlight important findings on the impacts of these programs while also uncovering some vulnerabilities in social protection programming in Africa. We finally draw important lessons related to the delivery, targeting and impact of various social protection programs launched in Africa in response to the pandemic.